2013
DOI: 10.1002/clen.201300113
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Age of Permeable Pavements on Their Infiltration Function

Abstract: This study describes field investigations designed to compare the infiltration capacities of 55 permeable pavement systems installed in the Netherlands and in Australia. The ages of the pavements varied from 1 to 12 years. Using infiltrometer testing, the performance of the pavements has been compared in terms of their ability to infiltrate a three month average recurrence interval storm event in the case of the Australian pavements or the minimum specification for European infiltration capacities of 97.2 mm/h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
44
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 18 publications
6
44
0
Order By: Relevance
“…Due to a number of malfunctions related to local power outage, software problems and defective instruments, we report a continuous monitoring period of 12 months starting from 1 December 2014, i.e., to a starting point 19 months after completion of installation, thus initial high surface permeability rates were assumed to have settled to a more permanent level [9,22,23], providing results representative of a longer period of functional lifetime. The stalls were enrolled in the present maintenance program for surrounding conventional pavements, which includes occasional collection of litter and debris, but no specific actions to maintain high surface permeability.…”
Section: Methodsmentioning
confidence: 99%
“…Due to a number of malfunctions related to local power outage, software problems and defective instruments, we report a continuous monitoring period of 12 months starting from 1 December 2014, i.e., to a starting point 19 months after completion of installation, thus initial high surface permeability rates were assumed to have settled to a more permanent level [9,22,23], providing results representative of a longer period of functional lifetime. The stalls were enrolled in the present maintenance program for surrounding conventional pavements, which includes occasional collection of litter and debris, but no specific actions to maintain high surface permeability.…”
Section: Methodsmentioning
confidence: 99%
“…The presence of leakage from drinking water and sewer networks can increase infiltration to groundwater and amount of contaminants that is spread from the sewer system into the soil (Salvadore et al, 2015). Although it is well known that not all rainfall turns into runoff (Boogaard et al, 2013;Lucke et al, 2014), it is common to consider the losses from impervious areas so small that they can be assumed negligible compared to the total runoff volume (Ragab et al, 2003;Ramier et al, 2011). Ragab et al (2003) tried to emphasize the importance of ac-counting for infiltration in the urban water balance, and found that infiltration through the road surface can constitute between 6 and 9 % of annual rainfall.…”
Section: Groundwater Recharge and Subsurface Processes In Urban Areasmentioning
confidence: 99%
“…Ragab et al (2003) tried to emphasize the importance of ac-counting for infiltration in the urban water balance, and found that infiltration through the road surface can constitute between 6 and 9 % of annual rainfall. Due to high spatial variability of infiltration, representative measurements are difficult to obtain and require a large amount of point-scale measurements (Boogaard et al, 2013;Lucke et al, 2014).…”
Section: Groundwater Recharge and Subsurface Processes In Urban Areasmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this process has also been shown to reduce the hydraulic performance of PICPs over time due to clogging [1,2,7]. Although infiltration rates of newly installed pavements have been shown to be high [9][10][11] these rates are known to diminish over time due to clogging, potentially leading to a decrease in useful lifespan, more maintenance and higher replacement costs [12,13]. Accelerated surface clogging can lead to more frequent maintenance intervals and increased costs.…”
Section: Introductionmentioning
confidence: 99%